Formation of the gut in the first two naupliar stages of Acartia clausi and Hemidiaptomus roubaui (Copepoda, Calanoida): Comparative structural and ultrastructural aspects. - Baud, A., R.M. Barthélémy, S. Nival & M. Brunet (Canadian Journal of Zoology, 2002)
In this study, the structure and ultrastructure of the digestive system are compared in the early larval stages (nauplii I and II) of two copepod calanoid species, Acartia clausi Giesbrecht, 1889 and Hemidiaptomus roubaui Richard, 1888. The nauplii I of both species have no functional digestive tract, which is represented initially only by a blind esophageal slit and yolky endodermal cells, which fill the most part of the naupliar body, whereas at the nauplius II stage the differentiated digestive tract becomes functional. The resorption cavity corresponding to the future midgut is progressively formed in the endodermal mass during the premolt phase; it is surrounded by differentiating epithelial cells. In the ecdysial phase the foregut has associated labral glands, the midgut young R-, B-, and R'-cells of epithelium, and there is a short open hindgut.